Nonlinear Dynamics — 2016 - (:unkn) unknown (National Technical University "Kharkov Polytechnic Institute", 2016)
The book of Proceedings includes extended abstracts of presentations on 5th International Conference on Nonlinear Dynamics dedicated to 90th anniversary of Academician V. L. Rvachev.
Нелінійна динаміка — 2016
Keywords: Dynamics of Discrete Systems; Dynamics of Distributed Systems; Mini-Simposium on R-Functions; Nonlinear Dynamics; конференції НТУ "ХПІ"; праці вчених НТУ "ХПІ"; конференція з нелінійної динаміки; нелінійна динаміка